From Lonely to Resilient through Humanoid Robots: Building a New Framework of Resilience - Johan F. Hoorn (Journal of Robotics)
This paper connects different theories and methods from the social sciences and applies them to human-humanoid robot interaction (HHRI) to explain loneliness reduction and the build-up of resilience in older adults through social robots. It allows for user-related aspects such as age, social connectedness, gender role, personality, and need satisfaction as well as robot-related aspects, particularly coaching behaviors and communication styles. From these scientific considerations, solutions to design challenges are pinpointed, proposing novel interaction schemes that enhance the feeling of support and companionship. This paper also opens the way to conducting empirical research to examine HHRI-related designs, measuring user experience in HHRI, while suggesting applications in HHRI in various settings, such as coaching and eldercare.